2012
DOI: 10.5005/jp-journals-10005-1165
|View full text |Cite
|
Sign up to set email alerts
|

Ectodermal Dysplasia: A Genetic Review

Abstract: Ectodermal dysplasia is a rare hereditary disorder with a characteristic physiognomy. It is a genetic disorder affecting the development or function of the teeth, hair, nails and sweat glands. Depending on the particular syndrome ectodermal dysplasia can also affect the skin, the lens or retina of the eye, parts of the inner ear, the development of fingers and toes, the nerves and other parts of the body. Each syndrome usually involves a different combination of symptoms, which can range from mild to severe. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 11 publications
(9 reference statements)
0
44
0
2
Order By: Relevance
“…It was suggested that Cephalometric analysis has a favorable effect on the growth of maxilla and mandible following the placement of dentures. [ 11 ] Future trial of Recombinant EDA-A1 administration is going on to correct the features of XLHED. [ 11 ] Prenatal diagnosis can be performed using mutation analysis by chorionic villus sampling at 11–12 weeks of pregnancy or indirect prenatal diagnosis may be performed by linkage analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that Cephalometric analysis has a favorable effect on the growth of maxilla and mandible following the placement of dentures. [ 11 ] Future trial of Recombinant EDA-A1 administration is going on to correct the features of XLHED. [ 11 ] Prenatal diagnosis can be performed using mutation analysis by chorionic villus sampling at 11–12 weeks of pregnancy or indirect prenatal diagnosis may be performed by linkage analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Future trial of Recombinant EDA-A1 administration is going on to correct the features of XLHED. [ 11 ] Prenatal diagnosis can be performed using mutation analysis by chorionic villus sampling at 11–12 weeks of pregnancy or indirect prenatal diagnosis may be performed by linkage analysis. In conclusion, an early diagnosis of HED and dental treatment is an essential part of the management because the psychological factor is always there in the absence of teeth thus dentures will give a psychological boost to the self-image of the child.…”
Section: Discussionmentioning
confidence: 99%
“…At clinical and radiographic examination, no missing teeth were found. The mother also presented few facial features, but the dental involvement was remarkable with 11,12,16,17,18,21,22,25,26,28,45,46,47,48,35, 36, 37, 38 missing teeth. The mother reported in the anamnesis that in adolescence she also had several missing teeth, which suggests that she also presented EDH.…”
Section: Case Reportmentioning
confidence: 99%
“…What differs one form of disease from the other is the alteration degree in the glands and the genetic transmission 11 . EDs are caused by specific genes mutations 12 or specific chromosome coupling 13 . In most cases, the syndrome has a recessive character linked to the X chromosome 6 , and may also be transmitted as an autosomal dominant chromosome 4 or autosomal recessive chromosome [14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Ectodermal dysplasias (ECD) are inherited disorders characterized by abnormal morphogenesis of ectoderm 15 . Ectoderm is one of the three primary germ layers during the development of early embryo.…”
Section: I2 Ectodermal Dysplasia Disordersmentioning
confidence: 99%